(2x+3y-4z)-(x-y-z)=

Simple and best practice solution for (2x+3y-4z)-(x-y-z)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+3y-4z)-(x-y-z)= equation:


Simplifying
(2x + 3y + -4z) + -1(x + -1y + -1z) = 0

Remove parenthesis around (2x + 3y + -4z)
2x + 3y + -4z + -1(x + -1y + -1z) = 0
2x + 3y + -4z + (x * -1 + -1y * -1 + -1z * -1) = 0
2x + 3y + -4z + (-1x + 1y + 1z) = 0

Reorder the terms:
2x + -1x + 3y + 1y + -4z + 1z = 0

Combine like terms: 2x + -1x = 1x
1x + 3y + 1y + -4z + 1z = 0

Combine like terms: 3y + 1y = 4y
1x + 4y + -4z + 1z = 0

Combine like terms: -4z + 1z = -3z
1x + 4y + -3z = 0

Solving
1x + 4y + -3z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4y' to each side of the equation.
1x + 4y + -4y + -3z = 0 + -4y

Combine like terms: 4y + -4y = 0
1x + 0 + -3z = 0 + -4y
1x + -3z = 0 + -4y
Remove the zero:
1x + -3z = -4y

Add '3z' to each side of the equation.
1x + -3z + 3z = -4y + 3z

Combine like terms: -3z + 3z = 0
1x + 0 = -4y + 3z
1x = -4y + 3z

Divide each side by '1'.
x = -4y + 3z

Simplifying
x = -4y + 3z

See similar equations:

| 6y+14=15-9y+14 | | 3(x-7)=8 | | -x-29=-13+2x | | x-9+x=3 | | -x-29=-12x-1 | | 4x^3+20x+10=0 | | y^2-14y=-36 | | 42x+50=1500 | | 2x^2+10x=-15 | | -10=4(x-5)+6x | | 2y+2(y-2)=7y-5(y-10) | | 2x^2+10x=15 | | 70=6x+5x-7 | | 4(-5-5x)=-200 | | 40+273= | | (2y+5)(3y+7)= | | 2(-5+x)=14 | | -8(x+1)+5(3x-4)=6(x-6)+14 | | 10ac*6ab*(-2bc)= | | 6(8+x)=6 | | 2x^2+3x=4 | | 14x+32=70 | | 6x-6-3x=-18 | | 6(-11+2n)-2n=-7(-n+3) | | 2(6+7x)=68 | | 0.75a+14=8 | | 5t-4=4+t | | 5(6x-10)=-20 | | (8a^2-6a-8)-(-6a^2+7a+5)= | | 4(n-6)-(2-3n)=6n | | 4x+1=34+7x | | (x-2)(x+6)=3x |

Equations solver categories